Oxidative stress in the pathogenesis of keratoconus - Wójcik, Katarzyna A.; Błasiak, Janusz; Kurowska, Anna; Szaflik, Jerzy; Szaflik, Jacek P. (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Keratoconus is a non-inflammatory corneal disease, which involves changes of the corneal shape, due to thinning of the corneal stroma. The pathogenesis of this disease has remained unclear, but results of many studies indicate that keratoconus is a multifactorial disease. It is hypothesized, that this disorder is associated with both genetic and environmental factors. An increase in toxic products of lipid peroxidation and nitric oxide pathways, as well as decreased levels of some enzymatic and non-enzymatic antioxidants seen in keratoconus, suggest an important role of oxidative stress in the pathogenesis of this disease. It seems that the interactions of reactive oxygen and nitric species with cellular components including nucleic acids, membranę lipids and proteins, may activate a series of events leading to keratoconus. The excess amount of reactive oxygen and nitric species may induce mitochondrial DNA (mtDNA) damage, the extent of which increases in corneas with keratoconus. This damage may disturb the mitochondrial process of oxidative phosphorylation, resulting in further increase in formation of reactive oxygen and nitric species. Furthermore, some elements of oxidative stress can be involved in the activation of certain proteinases and release of lysosomal enzymes, which may be important for corneal thinning in keratoconus.